The Cambridge companion to the literature of the Crusades - Bale, Anthony Paul, 1975- (Cambridge : Cambridge University Press, 2019)
How were the crusades, and the crusaders, narrated, described, and romanticised by the various communities that experienced or remembered them? This Companion provides a critical overview of the diverse and multilingual literary output connected with crusading over the last millennium, from the first writings which sought to understand and report on what was happening, to contemporary Medievalism in which crusading is a potent image of holy war and jihad. The chapters show the enduring legacy of the crusaders' imagery, from the chansons de geste to Walter Scott, from Charlemagne to Orlando Bloom. Whilst the Crusaders' hold on Jerusalem was relatively short-lived, the desire for Jerusalem has had a long afterlife in many cultural contexts and media.
Title from publisher's bibliographic system (viewed on 04 Jan 2019).
Keywords: Crusades in literature